Aktualisasi Keterampilan Interpersonal Kepala Sekolah Dalam Meningkatkan Aktivitas Kinerja Guru - Sania Zahra; Lala Dalalah; Fatan Abdul Rozak; Anis Fauzi (IAIN Ternate, 2023)
The success of an educational leader is to create an effective and efficient organization. A leader in a school is also called a school principal, where the principal has important duties and responsibilities in managing and managing the conditions and conditions of the school so that it can run with the goals that have been set. An effective leader is a leader who has good interpersonal communication between teachers and other staff. Interpersonal communication is needed by a teacher and a principal in order to create a good situation. A teacher should not be allowed to work in the absence of communication with the principal or his leader. With good communication, it will increase the effectiveness and performance of teachers in teaching.